IMPLEMENTASI KEBIJAKAN TENTANG PENCATATAN PERNIKAHAN DI KEMENTERIAN AGAMA KABUPATEN CIAMIS (Studi Implementasi Peraturan Menteri Agama Nomor 20 Tahun 2019) - Rustaman, Maman (Journal of Management Review, 2025)
This research is motivated by the fact that the Regulation of the Minister of Religious Affairs concerning Marriage Registration is the latest legal basis governing the procedures, requirements, and mechanisms for marriage registration. This policy aims to realize orderly marriage administration, provide legal certainty for husbands, wives, and children, and improve service quality to the community. Ciamis Regency, as one of the regions with a significant Muslim population, has its own dynamics in the implementation of marriage registration policies. The purpose of this research is to describe and analyze the implementation of marriage registration policies through Permenag at the Ciamis Regency Religious Affairs Office. This research uses a qualitative approach with a descriptive method. The research data were obtained from the Ciamis Regency Religious Affairs Office, Heads of the Religious Affairs Office at the sub-district level, and staff of the Religious Affairs Office at the sub-district level. Data collection instruments used in this research were interviews, observation, and documentation studies, as well as conducting triangulation. Furthermore, the data were processed through data reduction, data presentation, conclusion drawing, and data verification. The conclusions of this research indicate that the effective policy implementation design in marriage registration through Permenag at the Ciamis Regency has been carried out consistently and sustainably; Effective communication in the implementation of marriage registration policies through Permenag at the Ciamis Regency Religious Affairs Office is evident; The support and commitment of leaders in the implementation of marriage registration policies through Permenag at the Ciamis Regency Religious Affairs Office include: the support and commitment of the Head of Islamic Community Guidance Section, Heads of Religious Affairs Offices at the sub-district level, and staff of the Religious Affairs Offices at the sub-district level still need to be improved; factors influencing the support and commitment of leaders: policy understanding, availability of resources, and organizational culture; and the support and commitment of leaders have a positive influence on improving the quality of public services at the Ciamis Regency Religious Affairs Office; Improving the quality of public services at the Religious Affairs Offices at the sub-district level through the implementation of marriage registration policies through Permenag by the Ciamis Regency Religious Affairs Office still requires attention and serious efforts; The participation and involvement of stakeholders in the implementation of marriage registration policies through Permenag by the Ciamis Regency Religious Affairs Office in improving the quality of public services at the Religious Affairs Offices at the sub-district level is still not optimal; and Continuous monitoring and evaluation have been carried out to evaluate the implementation of marriage registration policies through Permenag by the Ciamis Regency Religious Affairs Office in improving the quality of public services.